Development of ICT strategic plan for smart school in Iran (case study : Ministry of Education in Iran) - Omidinia, Siavash (2009)
The purpose of this project is on development of ICT Strategic Plan for Iran Secondary education (Specially High School) in order to define a roadmap for establishing a standard infrastructure and platform for using ICT in teaching and learning at this level of education. In Iran, currently we are running 4th five year national development plan. The qualitative goals of government of Iran in this plan have included developing e-enabled national services such as e-commerce, e-learning, e-health, and egovernment. Based on my finding in Malaysian Smart School Pilot project and its success, Iran will benefit from customizing and applying practices of Malaysia in development of both smart schools and the ICT Strategic Plan for smart schools. The reason is Smart School Pilot project and its successor, the four waves roadmap for converting all schools to smart schools in Malaysia were executed and successfully have been performed. In Iran, Smart schools efforts recently have been started by selecting around 100 schools in main cities of states. This activity is based on the results of four sample schools that had equipped earlier. By visiting these initiatives and studying latest practices of Malaysia, the author realized that for succeeding and speeding up smart school development in Iran, an integrated ICT plan should be provided. This plan will coordinate Ministry of Education and other stakeholders such as schools administrators, ICT staffs and local participants to follow a standard, effective and efficient path for implementing smart schools.